Elevated truncated oxidized phospholipids as a factor exacerbating ALI in the aging lungs. Issue 3 (6th December 2018) - Ke, Yunbo; Karki, Pratap; Kim, Junghyun; Son, Sophia; Berdyshev, Evgeny; Bochkov, Valery N.; Birukova, Anna A.; Birukov, Konstantin G.
ABSTRACT: As mechanisms controlling redox homeostasis become impaired with aging, exaggerated oxidant stress may cause disproportional oxidation of cell membranes and circulating phospholipids (PLs), leading to the formation of truncated oxidized PL products (Tr‐OxPLs), which exhibit deleterious effects. This study investigated the role of elevated Tr‐OxPLs as a factor exacerbating inflammation and lung barrier dysfunction in an animal model of aging. Mass spectrometry analysis of Tr‐OxPL species in young (2–4 mo) and aging (18–24 mo) mice revealed elevated basal levels of several products [1‐palmitoyl‐2‐(5‐oxovaleroyl)‐ sn ‐glycero‐phosphocholine (POVPC), 1‐palmitoyl‐2‐glutaroyl‐ sn ‐glycero‐phosphocholine, lysophosphocholine, 1‐palmitoyl‐2‐(9‐oxo‐nonanoyl)‐ sn ‐glycero‐3‐phosphocholine, 1‐palmitoyl‐2‐azelaoyl‐ sn ‐glycero‐3‐phosphocholine, O‐1‐O‐palmitoyl‐2‐O‐(5, 8‐dioxo‐8‐hydroxy‐6‐octenoyl)‐l ‐glycero‐3‐phosphocholine, and others] in the aged lungs. An intratracheal (i.t.) injection of bacterial LPS caused increased generation of Tr‐OxPLs in the lungs but not in the liver, with higher levels detected in the aged group. In addition, OxPLs clearance from the lung tissue after LPS challenge was delayed in the aged group. The impact of Tr‐OxPLs on endothelial cell (EC) barrier compromise under inflammatory conditions was further evaluated in the 2‐hit cell culture model of acute lung injury (ALI). EC barrier dysfunction caused by cell treatment with a cytokine mixture (CM) was augmented by cotreatment with low‐dose Tr‐OxPLs, which did not significantly affect endothelial function when added alone. Deleterious effects of Tr‐OxPLs on inflamed ECs stimulated with CM were associated with further weakening of cell junctions and more robust EC hyperpermeability. Aged mice injected intratracheally with TNF‐α exhibited a more pronounced elevation of cell counts and protein content in bronchoalveolar lavage (BAL) samples. Interestingly, intravenous administration of low POVPC doses—which did not affect BAL parameters alone in young mice exposed to i.t. TNF‐α challenge—augmented lung injury to the levels observed in aged mice stimulated with TNF‐α alone. Inhibition of Tr‐OxPL generation by ectopic expression of PL‐specific platelet‐activating factor acetylhydrolase 2 (PAFAH2) markedly reduced EC dysfunction induced by CM, whereas PAFAH2 pharmacologic inhibition augmented deleterious effects of cytokines on EC barrier function. Moreover, exacerbating effects of PAFAH2 inhibition on TNF‐α–induced lung injury were observed in vivo . These results demonstrate an age‐dependent increase in Tr‐OxPL production under basal conditions and augmented Tr‐OxPL generation upon inflammatory stimulation, suggesting a major role for elevated Tr‐OxPLs in more severe ALI and delayed resolution in aging lungs.—Ke, Y., Karki, P., Kim, J., Son, S., Berdyshev, E., Bochkov, V. N., Birukova, A. A., Birukov, K. G. Elevated truncated oxidized phospholipids as a factor exacerbating ALI in the aging lungs. FASEB J. 33, 3887–3900 (2019). www.fasebj.org